Use of E-Wallet for Micro Small and Medium Enterprises (UMKM) Users - Rasmi Nur Anggraeni; Cahyaning Raheni (Universitas Muhammadiyah Palu, 2023)
What factors influence the interest of E-wallet users so that E-wallet service provider companies can determine what users value more when deciding to use the service, as well as develop and improve the quality of this payment system. This research is qualitative, namely, data that is described by category to produce a conclusion. This study shows that Micro, Small, and Medium Enterprises, apart from using cash transactions, also make transactions through E-wallets due to the large number of E-wallet users from consumers. In addition, E-wallets provide several conveniences for their users, including promos. Saving money is very safe, more accessible, and more practical.